Effect of Online Learning During the COVID-19 Pandemic on Tension-Type Headache, and Anxiety Among Medical Students - Esra Cinar Tanriverdi; Nuray Bilge; Yasemin Cayir (Haseki Tıp Bülteni)

(untitled)
Aim:Screen exposure can lead to numerous health problems, such as headaches, in students. This study aimed to investigate the impact of online learning on tension-type headache (TTH) and its association with anxiety among medical students who attended online classes during the novel coronavirus disease-2019 pandemic.Methods:This cross-sectional study was conducted between June 1 and 15, 2021, among preclinical medical students at the Ataturk University Faculty of Medicine in Erzurum. The data were collected via an online survey. Sociodemographic features and characteristics of online classes and headaches were collected. Anxiety levels were measured using the generalized anxiety disorder test-7 (GAD-7) scale. Questions for the preliminary diagnosis of TTH were prepared based on the International Classification of Headache Disorder Diagnosis.Results:The mean age of the participants was 20.6±3.0 years, and 52.2% (n=297) were women. Tension-type headaches affected 323 (56.8%) students, while 246 (43.2%) had no headaches. In addition, 41.3% (n=135) of the participants with TTH reported experiencing headaches after online classes, and 47.1% (n=154) of those with TTH stated that their headache intensity increased after online classes. The mean GAD-7 score was 11.2±5.2 among the participants with TTH, compared to 8.7±5.2 among those with no headache (p<0.01). Significant differences were observed between the groups in terms of daily screen time (p=0.019), GAD-7 score (p<0.001), and gender (p<0.001).Conclusion:The study findings indicate that TTH is common in medical students during online learning. Efforts should be made to educate students on screen use, and stress reduction programs should be included in the curriculum.